Friendshape - Rosenthal, Amy Krouse; Lichtenheld, Tom (New York : Scholastic Press, an imprint of Scholastic, Inc., 2015)
Presents a story of friends Triangle, Circle, Square, and Rectangle as they have fun together and support one another through life.
Keywords: Friendship -- Fiction; Shape -- Fiction; Friendship -- Fiction; Shape -- Fiction